Aplikasi Anybamba dengan Moperta untuk Meningkatkan Kemampuan Tolak Peluru pada Siswa Sekolah Menengah Pertama - Jujuk Arfianto (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objective was to improve the students’ weight throwing ability through bamboo weaving (anybamba) application with target game model (moperta). This research was designed as a classroom research included 32 eighth grade students in the Junior Secondary School 22 Surakarta. Data were collected through observation and analyzed descriptively and qualitatively. Data analysis results show that the students’ ability in weight throwing was improved through the application of bamboo weaving with target game model. The students’ ability increment was found as much as 89 %.